METROLOGICAL EVALUATION OF MEASUREMENT SYSTEM FOR TWO-PHASE FLOW FRACTIONS DETERMINATION USING 3D ELECTRICAL CAPACITANCE TOMOGRAPHY - Wajman, Radosław; Fidos, Henryk; Fiderek, Paweł; Jaworski, Tomasz; Nowakowski, Jacek; Sankowski, Dominik; Banasiak, Robert (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The industrial diagnostic and monitoring systems require new methods offering the possibility of non-invasive observation and analysis of the two-phase gas-liquid mixtures flows. The designed new measurement system is dedicated for non-invasive percentage phase distribution calculation and flow structure identification in the vertical and horizontal pipelines. This paper presents some research results of the metrological validation of the designed three-dimensional capacitance tomography measurement system including: the 3D ECT sensor structure optimization, the metrological analysis of the image reconstruction process accuracy and the metrological analysis of the results of the phase distribution calculation method in comparison with other common technics. As a result of performed analysis the height capability of the 3D ECT measurement system for non-invasive real time dynamic flow processes identification was proved.